2022
DOI: 10.3390/foods11131862
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antioxidant and Antiviral Activities of Hydroethanolic Extracts of Selected Lamiaceae Species

Abstract: Medicinal and aromatic plants (MAPs) are potential sources of natural bioactive phytochemical compounds of an incredible worth for the food industry, such as polyphenols. Lamiaceae medicinal and aromatic plants from Granada’s high plateau, concretely Origanum bastetanum, Thymus zygis gracilis, Thymus longiflorus, Thymus membranaceus and Ziziphora hispanica, were evaluated under different conventional solid–liquid extraction conditions to obtain extracts enriched in bioactive compounds. Phenolic profile was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…It was reported that the antiviral mechanism is provided by the number of hydroxyl groups present in the benzene ring. 33–35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the antiviral mechanism is provided by the number of hydroxyl groups present in the benzene ring. 33–35 …”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the antiviral mechanism is provided by the number of hydroxyl groups present in the benzene ring. [33][34][35] ADMET and Drug-Likeness Analysis Currently, computational studies are in the modeling stage of studying the drug's pharmacokinetics, including absorption, distribution, metabolism, excretion, and toxicity (ADMET). 36 Pharmacokinetics prediction of a compound needs to be seen using computational studies because this method is more cost-effective and more efficient.…”
mentioning
confidence: 99%
“…In a study conducted in Spain, the effect of ethanolic-aqueous extract of plant species belonging to different genera on FCV was investigated. Among the species used, it has been reported that plant species Origanum [91]. In this context, it is seen that the plants are effective against FCV.…”
Section: Feline Calicivirus (Fcv) (Genus: Vesivirus)mentioning
confidence: 98%
“…Although polyphenols were isolated from various plant parts [ 166 ], they are found at higher levels in the outer layers of tissues [ 167 ] as the production of these metabolites can be induced by both biotic and abiotic factors such as reactive oxygen and nitrogen species, insufficient amounts of nutrients, low temperatures, UV light, predators, parasites, pathogens, wounding, and other stress conditions [ 163 , 168 , 169 ]. Nevertheless, the antimicrobial potential of polyphenols has not been fully deciphered [ 170 ] due to the complexity of their natural mixtures in plants [ 171 ] and their inconsistent activity [ 172 ].…”
Section: Aromatic Plants As Biocontrol Agentsmentioning
confidence: 99%